Синтез багатомасової моделі баштового крану - Коваленко, Валентин Олександрович; Коваленко, Олег Олександрович; Стрижак, Всеволод Вікторович; Іглін, С. П.; Стрижак, Мар'яна Георгіївна (Одеський національний політехнічний університет, 2023)
Стаття присвячена дослідженню динаміки баштового крану з поворотною баштою. Розглядається синтез багатомасової динамічної моделі. Головним завданням дослідження і, відповідно, головним науковим результатом даної публікації є врахування маси приводу як окремого елемента.

A literature review was conducted, and it was established that a large number of works were devoted to the issue of crane dynamics, which in turn testifies to the relevance of studying this issue. The classic model for studying turning mechanisms based on the "boom-load" system on a flexible suspension does not fully reflect complex oscillatory processes and does not take into account the dynamic characteristics of the drive. The research is aimed at obtaining a multi-mass dynamic model of a tower crane with a rotating tower, which allows considering the drive as a separate mass. For this purpose, an analysis of the structure of a tower crane with a rotating tower was carried out, its constituent elements were determined, a calculation scheme was drawn up, where the drive of the turning mechanism is taken into account as a separate mass, a system of equations describing the movement of the considered mechanical system was obtained with the help of Lagrange equations. The main structural elements of the crane under study include: a supporting rotary device, a tower, a jib and a multi-splash system of a lifting mechanism with a suspended load. The drive and its dynamic characteristics are taken into account as a separate element. The further direction of research can be considered the verification of this model by calculation according to the parameters of a real crane and the comparison of the calculation results with the experimental data.
Synthesis of multimass model of tower crane
Keywords: кран; механізм повороту; динаміка; crane; rotation mechanism; dynamics